2014
DOI: 10.1016/j.redox.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses induced by 24S-hydroxycholesterol through liver X receptor pathway reduce 7-ketocholesterol-caused neuronal cell death

Abstract: Lipid peroxidation products have been known to induce cellular adaptive responses and enhance tolerance against subsequent oxidative stress through up-regulation of antioxidant compounds and enzymes. 24S-hydroxycholesterol (24SOHC) which is endogenously produced oxysterol in the brain plays an important role in maintaining brain cholesterol homeostasis. In this study, we evaluated adaptive responses induced by brain-specific oxysterol 24SOHC in human neuroblastoma SH-SY5Y cells. Cells treated with 24SOHC at su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 40 publications
(35 reference statements)
1
53
0
Order By: Relevance
“…In both undifferentiated and retinoic acid differentiated SH-SY5Y cells, pretreatment with 24-OHC resulted in a significant reduction in cell death induced by subsequent treatment with 7KC [56]. Although its main role is to maintain brain cholesterol homeostasis, it was reported that 24S-OHC could induce cell death in various cell types, despite its ability to reduce Ab1-42 production and 7KC cytotoxicity [18].…”
Section: Discussionmentioning
confidence: 99%
“…In both undifferentiated and retinoic acid differentiated SH-SY5Y cells, pretreatment with 24-OHC resulted in a significant reduction in cell death induced by subsequent treatment with 7KC [56]. Although its main role is to maintain brain cholesterol homeostasis, it was reported that 24S-OHC could induce cell death in various cell types, despite its ability to reduce Ab1-42 production and 7KC cytotoxicity [18].…”
Section: Discussionmentioning
confidence: 99%
“…When we treated undifferentiated SH-SY5Y cells with 24S-OHC, we observed that 24S-OHC exhibited cytotoxicity in a concentration-dependent manner (Fig. 1) [60,83,84]. 24S-OHC at concentrations higher than 10 M significantly caused cell death in which caspase-3 and caspase-9 were not activated [84].…”
Section: Direct Cytotoxicity Of 24s-ohc In Differentiated Sh-sy5y Celmentioning
confidence: 93%
“…Since the highly cytotoxic potential of 7-KC has been demonstrated in neuronal cells [57][58][59], 7-KC is suspected to be involved in the pathogenesis of neurodegenerative disease. In the case of 24S-OHC, stimulation of human neuroblastoma cell line (SH-SY5Y cells) with sublethal concentrations of 24S-OHC was found to induce adaptive response and protect the cells against subsequent cytotoxic stress induced by 7-KC [60]. The cytoprotective effect of 24S-OHC disappeared in LXR-knocked-down cells, suggesting that LXR played a key role in 24S-OHC-induced adaptive response.…”
Section: Mechanism Of Protection Of Neuronal Cells By 24s-ohcmentioning
confidence: 98%
See 1 more Smart Citation
“…These complementary data obtained by flow cytometry and confocal microscopy suggest topographical modifications and clustering of CYP46A1 which could contribute to increase the activity of the enzyme, leading to higher 24S-OHC production. As 24S-OHC is a potent LXR agonist, which can counteract lipid induced cytotoxicity (especially 7KC-induced cell death of SH-SY-5Y neuronal cells via up-regulation of the ATP-binding cassette transporter A1 (ABCA1) [17], increased cellular level of 24S-OHC could occur as an adaptative response to neuronal damages. However, 24S-OHC can also increase amyloid toxicity in vitro by increasing oxidative stress [18].…”
mentioning
confidence: 99%